New insights into colloidal gold flakes: structural investigation, micro-ellipsometry and thinning procedure towards ultrathin monocrystalline layers. Issue 8 (14th December 2015) - Hoffmann, B.; Bashouti, M. Y.; Feichtner, T.; Mačković, M.; Dieker, C.; Salaheldin, A. M.; Richter, P.; Gordan, O. D.; Zahn, D. R. T.; Spiecker, E.; Christiansen, S.
Abstract : We present details about the intrinsic structure and optical properties of gold flakes which can be used in plasmonic applications. Ultrathin crystalline layers were fabricated. Abstract : High-quality fabrication of plasmonic devices often relies on wet-chemically grown ultraflat, presumably single-crystalline gold flakes due to their superior materials properties. However, important details about their intrinsic structure and their optical properties are not well understood yet. In this study, we present a synthesis routine for large flakes with diameters of up to 70 μm and an in-depth investigation of their structural and optical properties. The flakes are precisely analyzed by transmission electron microscopy, electron backscatter diffraction and micro-ellipsometry. We found new evidence for the existence of twins extending parallel to the Au flake 111 surfaces which have been found to not interfere with the presented nanopatterning. Micro-Ellipsometry was carried out to determine the complex dielectric function and to compare it to previous measurements of bulk single crystalline gold. Finally, we used focused ion beam milling to prepare smooth crystalline layers and high-quality nanostructures with desired thickness down to 10 nm to demonstrate the outstanding properties of the flakes. Our findings support the plasmonics and nano optics community with a better understanding of this material which is ideally suited for superior plasmonic nanostructures.